هاجس الذات والرواية التجريبية - بلعزوقي, محمد (جامعة الوادي - University of Eloued, 2023)
تُعدُّ الرواية التجريبية ثورة على الأشكال والمضامين الروائية القديمة الكلاسيكية، إذ ترفض المحاكاة ، ولا تعترف بالنموذج، فتنفتح على مختلف السياقات الثقافية والمعرفية، وإن كنّا لا ننكر أن الرواية التجريبية تستعين بالمنجز الفني كمرجعية لبناء شكلها المفتوح؛ إلا أنها تسعى دائما إلى تجاوز ماهو كائن إلى مايمكن أن يكون؛ فهي دائمة التململ والبحث عن أشكال وتقنيات جديدة غير مطروقة، وعن مضامين بكر، تنبع من روح العصر وتستجيب لتطلعات الذائقة الأدبية؛ فما التجريب إلا استراتيجية تهدف إلى التجديد والخروج عن المألوف والنزوع نحو التفرّد الذي يعطي للأدب قيمته الإبداعية المتجددة. وما يهمنا في هذا البحث هو هاجس الذات في الرواية التجريبية، وبعبارة أخرى ارتباط الذاتية بالتجريب في الرواية. Abstract : The experimental novel is considered as a revolution against the old classical forms and contents, as it rejects simulation, and does not recognize a model, so it opens up to various cultural and cognitive contexts, although we do not deny that the experimental novel uses the artistic achievement as a reference to build its open form; However, it always seeks to transcend what is to what it could be; It is constantly fidgeting and searching for new, uninhibited forms and techniques, and virgin contents, stemming from the spirit of the age and relating to the writer’s self and responding to the aspirations of the literary taste; Experimentation is nothing but a strategy that aims at renewal and departure from the norm and the tendency towards exclusivity that gives literature its renewed creative value. What concerns us in this research is the obsession of the self in the experimental novel, in other words the connection of subjectivity to experimentation in the novel. Keywords : Obsession, Self, Subjectivity. Experimentation. Novel. Imagination..
مقال
Keywords: هاجس ; الذات ; الذاتية ; التجريبية ; التخييل ; الرواية